Darunnajah Islamic Boarding School Jakarta in the Framework of Society 5.0: Uniting Tradition and Technology in the Curriculum - Fauzia, Elita; Zudi, Muh; Maftuhah (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
Islamic boarding schools (Pesantren) are traditional Islamic educational institutions that have played a vital role in shaping the character, spirituality, and intellectuality of Muslims in Indonesia. However, technological advances and current social transformations require Islamic boarding schools to adapt quickly to remain relevant and contribute to modern society. Technological transformation in the Society 5.0 era encourages all sectors, including Islamic education, to integrate advanced technology with humanitarian values. As educational institutions based on Islamic tradition, Islamic boarding schools face significant challenges and opportunities in responding to the demands of an increasingly digitalized and automated society. This article discusses how Darunnajah Islamic Boarding School, as a modern Islamic boarding school, adapts to the Society 5.0 paradigm by developing a curriculum that combines traditional values and technological innovation with the principles of digital learning and a human-centered society as idealized in the Society 5.0 concept. Using an exploratory qualitative approach, this study relies on interview data, documentation, and literature review with a comparative analysis of Deguchi's Society 5.0 theory and Bernie Trilling's 21st-century skills theory. This study shows that Darunnajah Islamic Boarding School has made significant innovations in designing a curriculum that prioritizes life skills, digital literacy, and comprehensive Islamic character formation. This is realized through the implementation of the Tarbiyatul Muallimin Al-Islamiyah (TMI) curriculum which is based on the values of Maqashid al-Syari'ah, integration of digital technology, and strengthening 21st-century competencies.